THE TEACHER PERFORMANCE APPRAISAL SYSTEM IN IMPROVING TEACHERS PERFORMANCE IN LIMBOTO DISTRICT - Azis Rachman; Imam Mashudi; Aan August Bone (Governance: Jurnal Ilmu Administrasi Publik, 2021)
This study aims to: 1) Know and analyze the teacher performance appraisal system in improving teacher performance in Limboto District;2) Knowing and analyzing the factors that determine the success of the teacher performance appraisal system in improving teacher performance in Limboto District. The method used in this research is descriptive qualitative method. The research subjects were junior high school teachers in Limboto District, Gorontalo District. This research technique is observation, interview and documentation, namely primary data (data directly obtained from the source, through interviews) and secondary data (data obtained indirectly from the source, through documents or written notes). The data analysis technique used in this study was the interactive analysis model from Milles and Huberman. The data validity test includes credibility, transferability, dependability, and confirmability tests. The conclusion of this research is that the Teacher Performance Assessment System used will be very practical if it is supported by the internet network. As for schools that are not connected to the network, they can carry out input in areas that have a network. In addition, this application is very easy to use, the use process is light because there are not many features and is very simple to use, so that it can improve the performance of teachers in Limboto District.